Translation techniques applied on the journey of becoming a future translator - Araujo Martínez, Arminda Soledad; Dueñas Álvarez, Edgardo Antonio; Navarro Buendía, David Ernesto (Universidad de El Salvador. Facultad de Ciencias y Humanidades., 2025)
Disponible en soporte impreso